Effect of welding speed on micro-friction stir lap welding of ultra-thin aluminium and copper sheets - Kok, Chee Kuang; Jazayerli, Moumen Mahmoud; Por, Kia Wang; Liew, Kia Wai; Sued, Mohammad Kamil; Ooi, Chin Chin (Springer Science and Business Media Deutschland GmbH, 2024)
In this work, the technical feasibility of micro-friction stir lap welding to join 0.5-mm ultra-thin aluminium and copper sheets was studied. After identifying the processability windows of important parameters such as plunge depth, welding speed and material positioning, the effect of welding speed to join the ultra-thin AA5052 and C11000 sheets was assessed. Welding speeds were varied from 50 to 400 mm/min. The relationship of the welding speed to the joint quality, such as microstructure, tensile lap shear strength, weld surface roughness and joint electrical resistance was elucidated. It was found that the dissimilar sheets only joined when the copper sheet was placed on top of the aluminium sheet. Feasible welding was found at welding speeds of 50 mm/min and 70 mm/min, a constant rotational speed of 1500 rpm and a plunge depth of 0.55 mm. The welds possessed similar average tensile lap shear strength of 16 to 18 MPa but differed in microstructure and joint electrical resistance. More visible stir zones with lamella bands were found in the microstructure of welds produced at 50 mm/min, indicating a higher degree of mixing, albeit with excessive flashes and tunnel defects near the joint interface. On the other hand, the welds produced at 70 mm/min exhibited limited mixing and lamellar intermetallic compounds. Tunnel defects were mostly at the advancing side within the copper layer, and hook defects were absent. With selected processing parameters, micro-friction stir welding ultra-thin copper sheets to aluminium sheets is demonstrably feasible for less critical applications.